Gambaran Karakteristik Dan Pengetahuan Ibu Hamil Tentang Anemia Di Wilayah Kerja Puskesmas Perawatan Namrole - Zubaeda Zubaeda; Siti Rochmaedah (Jurnal Kesehatan Amanah, 2020)
Anemia in pregnancy is anemia due to iron deficiensy, iron deficiency anemia in pregnant women is a health problem experienced by women all over the world, especially in developing countries. The Wold Health Organitation (WHO) reports that pregnant women who experience iron deficency are around 35-75% and it increases with increasing gestational age. Anemia is the most common health disorder in pregnancy according to WHO, the diagnosis of anemia in pregnosis is confirmed when the hemoglobin (Hb) level is < 11g/dL (7.45 mmol/L) and hematoric < 0.33. The prevalence of anemia in pregnant women worldwide is 41.8%. This study aims to describe the knowledge and characteristics of pregnant women obout anemia in the working area of the Namrole Nursing Health Center in 2020. This research is a descriptive research design using a cross sectional approach. The sampel is 80 respondents. The research instrumet used a questionnaire. The results of the research, the level of knowledge about anemia to be good in the Namrole Care Health Center in 2020.